EKONOMI NARKOTIKA DAN RESISTENSI KOLEKTIF TERHADAP APARAT PENEGAK HUKUM: SUATU KAJIAN MENGENAI DINAMIKA DALAM RELASI KEKUASAAN ANTARA NEGARA DAN MASYARAKAT DI PERUMAHAN PERMATA JAKARTA BARAT - ADITYA MUHAMMAD AKBAR, ADITYA MUHAMMAD AKBAR (Politika: Jurnal Ilmu Politik, 2013)
Perumahan Permata, a residential area located in West Jakarta commonly known asKampung Ambon, is an area plagued with high crime rate. The migrant community residingin this area are originally members of the lower class stratum who find employment invarious kinds of street crime activities. In the pas few years, Perumahan Permata raisesgrowing public concerns over the existence of an illicit economy fuelled by illegal drugstrafficking. The issue has not yet been utterly solved up until today since it involves anetwork of community based organized crime at the grass root level whuch never hesitatesto openly resist law enforcement efforts. This phenomenon signifies a shift in the existingstate-society power relations.By conducting a field research utilizing in-depth interviews and participatoryobservation author attempts to explore the socio-economic factors behind this phenomenon,in order to explain how the existing criminal network operates, as well as to explain howcollective resistance towards autjority might occur. Research findings show existingconnection between the development of narcotics economy and collective resistancetowards state authority in Perumahan Permata. Organized drufs trafficking increases thecapabilities of the resoective community to mobilize available power resources andeventually strengthens its position towards the state. On the other hand, ineffectivebehaviour of certain law enforcement officials who are secretly involved in criminal networksmakes it difficult for the state apparatus to gain legitimacy for taking repressive measures toimpose control over the illegal drugs trafficking acrivities in the area.Keyword : State – Society, Power Relation